Tanggung Jawab Badan Usaha Milik Negara Dalam Kegiatan Ekonomi Pada Cabang-Cabang Produksi Yang Tidak Menguasai Hajat Hidup Orang Banyak - Nabila, Syadzwina Hindun (KANJOLI Business Law Review, 2023)
Analysuing the position of monopoly State-Owned Enterprises in the perspective of business competition law which could potentially give rise to barriers in business competition in particular concerning control over production branches are considered important and master his life much. Though it is excluded in law number 5 of 1999 concerning the prohibition of Monopolies and Anticompetitive Business practices are unhealthy, but that should not be considered a monopoly owned by the State-Owned Enterprises at the same time have the power over the market, and all the power over its own market not obliging him to carry on the practice of healthy competition. Existence of State-Owned Enterprises in the perspective of business competition law is the implementation of Article 33 of the Constitution of 1945, where the presence of the NRI Soes is a manifestation of the State's role in the national economy for the well-being of the people. The position of monopoly State-Owned Eterprises in the perspective of business competition law is still frequently abused the rights relating to the control of the State giving rise to unhealthy business competition. A monopoly held by State-Owned Enterprises should be stabilised so that serves as the market competition can run healthy. Criteria for State-Owned Enterprises can be given a monopoly in business competition law perspective, just look at the functions and Government intervention in the economy aimed at the earliest possible time the prosperity of the people. Criteria for State-Owned Enterprises can be given a monopoly should be seen from the form and objectives of the establishment of State-Owned Enterprises as well as the magnitude of the ownership of the Government's stake in it.